2016
DOI: 10.3389/fnhum.2016.00308
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Understanding the Relationship between Descending Pain Modulation, Motor Corticospinal, and Neuroplasticity Regulation Systems in Chronic Myofascial Pain

Abstract: Myofascial pain syndrome (MPS) is a leading cause of chronic musculoskeletal pain. However, its neurobiological mechanisms are not entirely elucidated. Given the complex interaction between the networks involved in pain process, our approach, to providing insights into the neural mechanisms of pain, was to investigate the relationship between neurophysiological, neurochemical and clinical outcomes such as corticospinal excitability. Recent evidence has demonstrated that three neural systems are affected in chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 54 publications
3
43
0
1
Order By: Relevance
“…The authors explained that lack of effects is likely due to refractoriness of pain and duration of disease since most of the patients enrolled had injury durations of 10 or more years. In addition, the limited number of [19][20][21][22][23][24][25][26] sessions and small sample size, may not have been sufficient to observe significant effects at follow-up. The second study, on low back pain, even though the sample size was large (n = 135), did not show significant differences between sham and active tDCS [58].…”
Section: Delayed Tdcs Effects On Pain Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors explained that lack of effects is likely due to refractoriness of pain and duration of disease since most of the patients enrolled had injury durations of 10 or more years. In addition, the limited number of [19][20][21][22][23][24][25][26] sessions and small sample size, may not have been sufficient to observe significant effects at follow-up. The second study, on low back pain, even though the sample size was large (n = 135), did not show significant differences between sham and active tDCS [58].…”
Section: Delayed Tdcs Effects On Pain Reductionmentioning
confidence: 99%
“…Several studies have shown that M1 stimulation leads to local and distant effects that result in pain reduction. For instance, stimulating M1 may counteract the lack of inhibition from M1, that could also be associated with pain reduction [22,23]. In addition, it also leads to changes in thalamic and cingulate activity [24], known to be related to pain processing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is essential to understand the pain in a broader setting. Aspects such as psychological vulnerabilities, which include anxiety, depression, catastrophism (Syrjala et al, 2014), and previous chronic pain, which may change the integrity of descending modulatory endogenous pathways (Botelho et al, 2016), impact on development, maintenance, and response to treatment.…”
Section: Causes and Impact Of Cancer Painmentioning
confidence: 99%
“…Chemical changes within the muscle may also lead to peripheral sensitization. MTPs can generate continual nociceptive traffic to induce central sensitization, cortical re-organization, and alterations in descending inhibitory pain pathways [32][33][34][35][36]. MTPs are associated with muscles in sustained contraction causing limited movement across joints [37].…”
Section: Introductionmentioning
confidence: 99%